Alagille syndrome with moyamoya disease (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
We report a 5 year old male child who presented with a history of progressive jaundice since infancy and generalized pruritus. He was also found to have typical triangular facies, posterior embryotoxon on both eyes, peripheral pulmonary stenosis and paucity of bile ducts in liver biopsy. Magnetic resonance angiography of brain showed typical features of moyamoya disease. The child was diagnosed as a case of Alagille syndrome. This particular syndrome with feature of moyamoya disease has been rarely reported.